2022
DOI: 10.1155/2022/7425142
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profile, Physicochemical Composition, and Sensory Properties of Atlantic Salmon Fish (Salmo salar) during Different Culinary Treatments

Abstract: This study was conducted to assess the effects of boiling, steaming, and oven-cooking on the fatty acid profile, physicochemical composition, and sensory properties of Atlantic salmon fish. The protein content of steamed (18.90%) and oven-cooked (20.59%) salmon was significantly higher than that of boiled (16.69%) and raw fish (14.73%). Analysis of the fatty acids profile revealed that steaming significantly ( p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
(102 reference statements)
0
8
1
Order By: Relevance
“…This result can be explained as the low amount of moisture in the oven environment and the high amount of evaporated water. There are studies informed that oven baked salmon meat has higher lipid percentage than steamed salmon meat vice versa moisture percentage (Larsen et al, 2010;Şengör et al, 2013;Fomena Temgoua et al, 2022). There was no statistically significant difference observed in the ash contents among all groups (P<0.05).…”
Section: Results Of Proximate Analysesmentioning
confidence: 83%
See 1 more Smart Citation
“…This result can be explained as the low amount of moisture in the oven environment and the high amount of evaporated water. There are studies informed that oven baked salmon meat has higher lipid percentage than steamed salmon meat vice versa moisture percentage (Larsen et al, 2010;Şengör et al, 2013;Fomena Temgoua et al, 2022). There was no statistically significant difference observed in the ash contents among all groups (P<0.05).…”
Section: Results Of Proximate Analysesmentioning
confidence: 83%
“…Global fisheries production has totally reached 177.8 million tonnes in 2019. Atlantic salmon (Salmo salar), that is a rich omega 3 long chain PUFAs resource, has a special place in the international seafood trade because of its 2.615 million tonnes production from aquaculture and 17.1 billion USD nominal value (FAO, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the content of amino acids is mainly dependent on the harvesting location, season, and processing techniques. For example, the protein contents of Atlantic salmon during different culinary treatments such as boiling, steaming, and oven-cooking were 16.69, 18.9, and 20.59%, respectively, while the raw fish had 14.73% protein [43]. They also reported that the major amino acids in cooked and raw salmon were aspartic acid and alanine.…”
Section: Protein and Amino Acid Compositionmentioning
confidence: 99%
“…The results of the ash content also have similarities with the research [17] on farmed rainbow trout, which produced ash content in the steaming treatment of 1.33% and the boiling treatment of 1.25%. According to [3], the ash content of marine fish was reduced after being boiled due to the volatile nature of mineral elements at high temperatures. The results of statistical tests on the value of blue swimming crab ash content obtained t-test results with the value of Sig.…”
Section: Ash Contentmentioning
confidence: 99%
“…Previous research on aquatic commodity quality characteristics such as sensory values, proximate analysis, amino acid and fatty acid profiles with different processing methods was also carried out on Atlantic salmon [3], higher PUFA values were produced in steaming treatment, while SFA and MUFA produced higher values in the boiling treatment, water content and amino acid profile were also higher in steaming than in boiling treatment. The purpose of this study was to determine and compare the amino acid profile, fatty acid profile, proximate analysis, and sensory value of blue swimming crabs which were processed with two different cooking method: steaming and boiling.…”
Section: Introductionmentioning
confidence: 99%